2015
DOI: 10.3233/wor-152159
|View full text |Cite
|
Sign up to set email alerts
|

The state of ergonomics for mobile computing technology

Abstract: Abstract. BACKGROUND:Because mobile computing technologies, such as notebook computers, smart mobile phones, and tablet computers afford users many different configurations through their intended mobility, there is concern about their effects on musculoskeletal pain and a need for usage recommendations. OBJECTIVE: Therefore the main goal of this paper to determine which best practices surrounding the use of mobile computing devices can be gleaned from current field and laboratory studies of mobile computing de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 43 publications
1
28
0
6
Order By: Relevance
“…The participants in the reviewed studies were primarily females (136 females and 116 males) and were in their 20s [2,5,8,11,[14][15][16][17][18][19][20][21][22]. Some of the study participants were more than 30 years old [11][12][13][14][15]; one study did not specify the age of the subjects. Eight articles indicated that the participants are right handed [2,16,18,20,21,[23][24][25][26][27].…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants in the reviewed studies were primarily females (136 females and 116 males) and were in their 20s [2,5,8,11,[14][15][16][17][18][19][20][21][22]. Some of the study participants were more than 30 years old [11][12][13][14][15]; one study did not specify the age of the subjects. Eight articles indicated that the participants are right handed [2,16,18,20,21,[23][24][25][26][27].…”
Section: General Characteristicsmentioning
confidence: 99%
“…The studies discussed above can serve as a guide for professionals and practitioners in defining the problems related to SP use and establishing the best approaches to preventing such problems as these studies demonstrate the potential damage mechanisms that underlie texting [13]. The aim of the current research was to systematically evaluate previous studies on the manner by which SPs are used and such musculoskeletal risk factors that explored by objective methods.…”
mentioning
confidence: 99%
“…Mobile smart technologies like tablet-pcs, smartphones, smartwatches and different variants of smart glasses, are on the rise in everybody's life [1]. Data for Germany, presented by Bitkom [2], indicate a rise of smartphone usage from 36 percent in 2012 to 65 percent in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…With the small touchscreens, thumbs can play a more prominent role in operating the device through multitouch gestures. There is a growing concern about detrimental impact on health associated with (extensive) use with respect to musculoskeletal disorders [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…Adentrar o território da escola para a realização de uma pesquisa relacionada à saúde não é tarefa fácil, tanto para a pesquisadora quanto para professores, alunos, dirigentes e funcionários que recebem a Sendo assim, pesquisas adicionais serão necessárias para avaliar o uso ergonômico desses dispositivos eletrônicos (Habibi e Soury, 2015;Gold et al, 2012b;Dennerlein, 2015) e sua disposição tanto em casa quanto nos locais de trabalho, pois a postura desses adolescentes parece ser de importância fundamental na utilização das múltiplas mídias digitais. …”
Section: Métodosunclassified